Myeloid Differentiation Primary Response 88–Cyclin D1 Signaling in Breast Cancer Cells Regulates Toll-Like Receptor 3-Mediated Cell Proliferation - Singh, Aradhana; Devkar, Ranjitsinh; Basu, Anupam (Frontiers in Oncology, 2020)
TLR3 mediated apoptotic changes in cancer cells are well documented and hence several synthetic ligands of TLR3 are being used for adjuvant therapy. But there are reports showing contradictory effect of TLR3 signaling which includes our previous report that had shown cell proliferation following surface localization of TLR 3. However, the underlying mechanism of cell surface localization of TLR3 and subsequent cell proliferation lacks clarity. This study addresses TLR3 ligand mediated signaling cascade that regulates a proliferative effect in breast cancer cells (MDA MB 231 and T47D) challenged with TLR3 ligand in the presence of MyD88 inhibitor. Evidences were obtained using immunoblotting, co-immunoprecipitation, confocal microscopy, Immunocytochemistry, ELISA, and flowcytometry. Results had revealed that TLR3 ligand treatment significantly enhanced breast cancer cell proliferation marked by an upregulated expression of cyclinD1 but the same were suppressed by addition of MyD88 inhibitor. Also, expression of IRAK1-TRAF6-TAK1 were altered in the given TLR3-signaling pathway. Inhibition of MyD88 disrupted the downstream adaptor complex and mediated signaling through TLR3-MyD88- NF-κB (p65)-IL6-Cyclin D1 pathway. TLR3 mediated alternative signaling of the TLR3-MyD88-IRAK1-TRAF6-TAK1-TAB1- NF-κB axis leads to upregulation of IL6 and cyclinD1. This response is hypothesized to be via the MyD88 gateway that culminates in proliferation of breast cancer cells. Overall, this study provides first comprehensive evidence on involvement of canonical signaling of TLR3 using MyD88 - Cyclin D1 mediated breast cancer cell proliferation. The findings elucidated herein will provide valuable insights into understand the TLR3 mediated adjuvant therapy in cancer.